Propuesta de marca turística para el cantón Espíndola, Provincia de Loja - Placencia Correa, Valeria Natalia (2023)
For the present work entitled "Proposal of a tourist brand for the Espíndola canton, province of Loja", the general objective was: To propose a tourist brand for the Espíndola canton, province of Loja. For the elaboration of the research work it was necessary to establish the following specific objectives: Diagnose the tourism reality of the Espíndola canton in order to determine the elements to be included in the tourism brand; the second objective is to conduct a proposal for a tourist brand that takes as a reference the most important characteristics of the Espíndola canton; Finally, the third objective is to propose strategies for the dissemination and positioning of the Tourism Brand of the Espíndola Canton. The analytical-synthetic method was applied as part of the methodology. Likewise, the techniques of PDOT, survey and SWOT were also used, which define the relevant characteristics for the design of the tourism brand proposal for the Espíndola canton. A brand test was applied to the target market, which is the population belonging to the urban parish of Espíndola, to determine whether the brand complied with the conceptual design and to adjust it if necessary. Finally, conclusions were drawn by objectives that allowed us to determine the representative characteristics of the tourist brand and define a brand design for the Espíndola canton, which can be used for tourism. Additionally, recommendations were made to the Espíndola cantonal GAD and the competent entity such as the Tourist Interpretation Center.